Predicting the outcomes of using longer‐acting prophylactic factor VIII to treat people with severe hemophilia A: a hypothetical decision analysis. (3rd October 2016) - Miners, A. H.; Krishnan, S.; Pasi, K. J.
Abstract : Essentials No randomized trials have compared long‐acting factor VIII (FVIII) with currently used products. A comparison was undertaken using a decision model to predict FVIII use and number of bleeds. In the base case, longer acting FVIII reduced factor use by 17% while resulting in similar bleeds. The value of longer acting FVIII will be largely determined by existing regimens and unit price. Click to hear Prof. Makris's presentation on new treatments in hemophilia Summary: Background: Recently, factor VIII (FVIII) products with longer half‐lives, such as recombinant FVIII Fc fusion protein (rFVIIIFc), have become available. Use of longer‐acting FVIII products will largely depend on effectiveness and cost; no direct evaluations have compared these parameters between conventional and longer‐acting FVIII therapies. Objectives: To present a hypothetical decision analysis, combining evidence from multiple sources to estimate bleeding frequency, resource use and cost of longer‐acting prophylactic products, such as rFVIIIFc, vs. conventional recombinant FVIII (rFVIII). Patients/Methods: The decision model used published pharmacokinetic parameters, bleeding frequency vs. time information below a 1‐IU dL −1 FVIII trough level, and adherence. Prophylactic treatment scenarios were modelled for a hypothetical patient with severe hemophilia A (<1 IU/dL) receiving rFVIIIFc or rFVIII. Results: Infusing twice weekly with rFVIIIFc 42.7 IU kg −1 per dose required less clotting factor than infusing every 56 h with rFVIII 33.75 IU kg −1 per dose; annual bleeding rates were similar. Base case analysis suggested that total FVIII costs were equated when rFVIIIFc cost 1.18 times more per IU than rFVIII, assuming similar adherence. Other modelled scenarios produced similar results, although differences in FVIII consumption were particularly sensitive to assumptions regarding frequency and dose of the rFVIII and rFVIIIFc regimens. For example, decreasing rFVIII from 33.75 IU kg −1 to 30 IU kg −1 per dose decreased the price factor to 1.05. Conclusions: Longer‐acting FVIII products may reduce FVIII consumption and infusion frequency without compromising hemostatic effect; this should be considered along with other factors (e.g. adherence and underlying FVIII regimen) when evaluating a suitable price for these agents.